Immobilized copper nanoparticles on nitrogen-rich porous activated carbon from egg white biomass: a robust hydrophilic–hydrophobic balance catalyst for click reaction. Issue 68 (19th November 2018) - Saeidian, Hamid; Khajeh, Saleh Vahdati; Mirjafary, Zohreh; Eftekhari-Sis, Bagher
Abstract : Nitrogen-rich porous carbon (NAC) material was synthesized from egg white biomass via pyrolysis, followed by chemical activation with KOH. Then, the copper nanoparticles were immobilized on the surface of the NAC by chemical reduction method. Abstract : Biomass conversion to carbonaceous materials and their use in various applications, such as capacitors, catalyst supports, and adsorbents, have attracted considerable attention from the viewpoint of green chemistry. In this regard, chicken egg white is one of the most important biomass, which can act as an in situ nitrogen doping source. In this paper, nitrogen-rich porous carbon material was synthesized from egg white biomass via pyrolysis at 600 °C under nitrogen atmosphere, followed by chemical activation with KOH at 500 °C. The results showed that the as-synthesized porous carbon material has a high content of nitrogen and high surface area, on which nitrogen can tune the surface hydrophobicity–hydrophilicity through interaction with water molecules. Then, the copper nanoparticles were immobilized on the surface of nitrogen-rich activated carbon by a chemical reduction method. Nanocatalyst structure was characterized by elemental analysis, TEM, AFM, Raman, FT-IR, porosimetry and atomic adsorption techniques. Finally, catalytic activity was evaluated for the one-pot synthesis of triazole in aqueous medium. The nanocatalyst offers some advantages such as excellent activity, low loading of catalyst, good yields of products and short reaction times.